Respostas
respondido por:
1
Pelo método da substituição, temos:
3x+y=31
y = 31 - 3x
-x -4y = 8
-x - 4(31 - 3x) = 8
-x - 124 + 12x = 8
11x = 132
x = 132/11
x = 12
y = 31 - 3x
y = 31 - 3(12)
y = 31 - 36
y = -5
-xy
-(12) . (-5)
-12 . -5
+60
3x+y=31
y = 31 - 3x
-x -4y = 8
-x - 4(31 - 3x) = 8
-x - 124 + 12x = 8
11x = 132
x = 132/11
x = 12
y = 31 - 3x
y = 31 - 3(12)
y = 31 - 36
y = -5
-xy
-(12) . (-5)
-12 . -5
+60
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás